IMPLEMENTASI PERANCANGAN ORGANISASI BERDASARKAN MARKET DRIVEN SEBAGAI STRATEGI PENGEMBANGAN INDUSTRI KREATIF PARIWISATA PERSPEKTIF MARKETING DAN KEBIJAKAN PUBLIK - Setia, Bayu Indra; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Pangestu, Erry S.R (Jurnal Agregasi, 2022)
The purpose of this research is to implement market-based organizational design as a creative tourism industry development strategy to promote tourist destinations. The creative economy not only contributes to several aspects of life from an economic perspective, but also has a positive effect on other aspects, namely social life, business environment, economic improvement and regional image. The method used is a qualitative method using a SWOT analysis of various data. This research produces several strategies that can be carried out by decision makers related to organizational design to get market driven with several strategies that can be developed, namely the development of a sustainable, community-based and comprehensive tourism creative industry, integrated between sectors, and between stakeholders. The concepts offered are the concept of ecotourism, halal tourism and Community-Based Tourism. So that everything can be carried out properly, it must be done with the marketing concept and the institutional concept. Keywords: market driven, creative industry , tourism.